Young People and Golden Rule Catholicism in the Philippines: The Case of Religiously Involved Filipino Students - Cornelio, Jayeel (Archīum Ateneo, 2014)
The condition of Catholicism in the Philippines presents nuances that can potentially enrich the understanding of Christianity in the world today. On one hand, the Philippines demonstrates the continuing vibrancy of Catholicism outside the supposedly secularized world of the West. Around 80% of the Philippine population is Catholic (National Statistics Office 2008), with 72.4% of Filipinos attending religious services at least two to three times a month, a participation rate which is vastly different even compared to Catholic countries in Europe, such as Italy (41.1%), Spain (27.5%) or Portugal (30.1%). (ISSP 2008) At the everyday level, fervent Catholic Charismatic movements such as El Shaddai (Kessler and Rüland 2008; Wiegele 2005) are quite common, as is pious devotion to the various iconographies of the Black Nazarene, the infant Jesus, Our Lady and the saints. (Cannell 1999; Bautista 2010) Re-enacted crucifixions are typical in the country and graphically portrayed in the media. (The Telegraph 2011) At the level of the religious institution, the perennial intervention of the Catholic Church in public issues such as divorce and artificial family planning is unmistakable. (Gloria 2008; Raffin and Cornelio 2009; Bautista 2010) Today, the continuing involvement of conservative Catholicism in state affairs is a political saga to behold. On the other hand, the Philippines presents itself as an interesting empirical site for the discovery of novel, even revolutionary, nuances within the Catholic Church.